In Vitro Pharmacological Activity Test on Pharmaceutical Biotechnology Products in The Form of Kombucha Bath Soap Pineapple Honey Subang As Antibacterial Gram Positive and Negative - Saraswati Prabawardani; M. Fariz Fadillah; Desi Trisnawati; Firman Rezaldi; K Kusumiyati; Irmawati Mathar (Jurnal Biologi Tropis, 2023)
One of the probiotic drinks produced by Scoby fermentation, namely Kombucha Honey Pineapple Subang, has been found as a source of gram-positive and gram-negative antibacterials in previous studies. In addition to its significance in the pharmaceutical (cosmetic) industry, Subang pineapple honey-based kombucha has the potential to be utilized as a functional food. Especially useful when making liquid body wash because it stops the growth of the skin-harming bacteria S. aureus, S. epidermidis, P. aeruginosa, and E. coli. The research was conducted with the intention of developing pharmaceutical biotechnology products in the form of liquid bath soap that contained the active ingredients of fermented kombucha solution and pineapple honey in concentrations of 15%, 25%, and 35%, respectively.This research method was a laboratory experiment using four soap-based preparations, including soap made from white sand with a sugar concentration of 15%, 25%, and 35%, a solution of fermented Kombucha Pineapple honey in Subang, and biore for market bath soap. The method used is disc diffusion. One-way ANOVA and post hoc analysis follow-up tests were used for data analysis. The study found that the most effective treatment for gram-positive and gram-negative bacteria was bath soap with a concentration of 35% of the active ingredient, kombucha fermented pineapple honey earring solution. The most recent advancement in preventing gram-positive and gram-negative bacteria from growing is the subject of this study.